An Empirical Equation to Predict the Porosity of Titanium Foams - Jian, Xiao; Hao, Cui; Guibao, Qiu; Yang, Yang (Characterization of Minerals, Metals, and Materials 2016, 2016)
Structural control is an interesting but less studied subject in titanium foam production using space holder technique. In this paper, an empirical equation was reported to predict the porosity of pure titanium foams. The empirical equation is P = 0.9SC + 0.011, where P and Sc represent porosity and spacer content, respectively. Results indicate that porosity is always lower than spacer content by approximately 10%. The porosities obtained from this method are also always lower than 90%.